Recirculation zone length in renal artery is affected by flow spirality and renal-to-aorta flow ratio. Issue 9 (4th July 2017) - Javadzadegan, Ashkan; Fulker, David; Barber, Tracie
Abstract: Haemodynamic perturbations such as flow recirculation zones play a key role in progression and development of renal artery stenosis, which typically originate at the aorta-renal bifurcation. The spiral nature of aortic blood flow, division of aortic blood flow in renal artery as well as the exercise conditions have been shown to alter the haemodynamics in both positive and negative ways. This study focuses on the combinative effects of spiral component of blood flow, renal-to-aorta flow ratio and the exercise conditions on the size and distribution of recirculation zones in renal branches using computational fluid dynamics technique. Our findings show that the recirculation length was longest when the renal-to-aorta flow ratio was smallest. Spiral flow and exercise conditions were found to be effective in reducing the recirculation length in particular in small renal-to-aorta flow ratios. These results support the hypothesis that in renal arteries with small flow ratios where a stenosis is already developed an artificially induced spiral flow within the aorta may decelerate the progression of stenosis and thereby help preserve kidney function.